An investigation of the growth status of 19-year-old Idesia polycarpa ‘Yuji’ plantation forest in the mountainous region of Henan, China - Pengcheng Li; Sohel Rana; Mengxing Zhang; Chao Jin; Kaixin Tian; Zhen Liu; Zhi Li; Qifei Cai; Xiaodong Geng; Yanmei Wang (Heliyon, 2023)
Plantation forests play an important role in the mitigation of greenhouse gas emissions. Idesia polycarpa Maxim is an emerging woody oil tree species in most Asian countries. The 19-year-old Idesia polycarpa ‘Yuji’ plantation forest was selected as a sample site. The nutrient contents of the understory soil total carbon (TC), total nitrogen (TN), nitrate nitrogen (NN), organic carbon (OC), available phosphorus (AP), available potassium (AK), and pH were analyzed. Several metrics were measured to quantify the growth status of the forest, such as tree heights (H), clear bole heights (CBH), diameters at breast height (DBH), and male-to-female ratios (MFR). In addition, we harvested the fruits to analyze oil content and fatty acid composition. The results found that the nutrient content of the soil was TC (4.93%), TN (0.42%), NN (43.08 mg kg−1), OC (4.90 g kg−1), AP (13.66 mg kg−1), AK (30.48 mg kg−1), and pH (7.90). The growth characteristics were H (11.75 m), DBH (12.79 cm), and CBH (6.17 m). The MFR was close to 1:1. Besides, the oil content of the fruit and unsaturated fatty acids was 24.08% and 68.49%, respectively. As an alternative tree species, the plantation of Idesia polycarpa offers great potential in artificial afforestation in some particular places with specific forest site conditions.